Changes of bacterial consortia in enrichment of deproteinized natural rubber with Sapa soil - Hoang Dung, Nguyen; Thi Thu Trang, Nguyen; Thi Thanh, Nguyen; Thi Quynh, Pham; Tien Thanh, Nguyen; Huong, Nguyen Lan (Vietnam Journal of Science and Technology, 2021)
The accumulation of rubber waste has become a major environmental issue worldwide due to its adverse effects on ecology. Bioremediation is focused to minimize this problem. In this study, the degradation of deproteinized natural rubber (DPNR) using bacterial consortia enriched from Sapa soil was examined. This soil was not history with rubber. The highest 39.16 ± 1.95 % weight loss of DPNR film was detected in the sixth enrichment consortium after 30 days of incubation. The occurrence of hydroxyl group in the film was observed by Fourier Transform Infrared Spectroscopy analysis. The changes in bacterial community in the consortia were determined by metagenomic analysis using 16S rRNA gene sequencing. The dominant phyla in all consortia were Actinobacteria, Bacteroidetes, and Proteobacteria, while the phylum Actinobacteria was key rubber-degraders in the consortia